Comparability of modern contraceptive use estimates between a face-to-face survey and a cellphone survey among women in Burkina Faso - Greenleaf, Abigail R. (PLoS One, 2020)
INTRODUCTION: The proliferation of cell phone ownership in Sub-Saharan Africa (SSA) presents the opportunity to collect public health indicators at a lower cost compared to face-to-face (FTF) surveys. This analysis assesses the equivalence of modern contraceptive prevalence estimates between a nationally representative FTF survey and a cell phone survey using random digit dialing (RDD) among women of reproductive age in Burkina Faso. METHODS: We analyzed data from two surveys conducted in Burkina Faso between December 2017 and May 2018. The FTF survey conducted by Performance Monitoring and Accountability (PMA2020) comprised a nationally representative sample of 3,556 women of reproductive age (15–49 years). The RDD survey was conducted using computer-assisted telephone interviewing and included 2,379 women of reproductive age. RESULTS: Compared to FTF respondents, women in the RDD sample were younger, were more likely to have a secondary degree and to speak French. RDD respondents were more likely to report using modern contraceptive use (40%) compared to FTF respondents (26%) and the difference remained unchanged after applying post-stratification weights to the RDD sample (39%). This difference surpassed the equivalence margin of 4%. The RDD sample also produced higher estimates of contraceptive use than the subsample of women who owned a phone in the FTF sample (32%). After adjusting for women’s sociodemographic factors, the odds of contraceptive use were 1.9 times higher (95% CI: 1.6–2.2) in the RDD survey compared to the FTF survey and 1.6 times higher (95% CI: 1.3–1.8) compared to FTF phone owners. CONCLUSIONS: Modern contraceptive prevalence in Burkina Faso is over-estimated when using a cell phone RDD survey, even after adjusting for a number of sociodemographic factors. Further research should explore causes of differential estimates of modern contraceptive use by survey modes.